Evidence-Based Caries Management for All Ages-Practical Guidelines - Featherstone, John D. B.; Crystal, Yasmi O.; Alston, Pamela; Chaffee, Benjamin W.; Doméjean, Sophie; Rechmann, Peter; Zhan, Ling; Ramos-Gomez, Francisco (Frontiers in Oral Health, 2021)
Introduction. The purpose of the present paper is to provide step-by-step guidelines for dental healthcare providers to manage dental caries based upon caries risk assessment (CRA) for ages 0-6 years and 6 years through adult. The manuscript reviews and updates the CAMBRA (caries management by risk assessment) system which includes CRA and caries management recommendations that are guided by the assessed risk level. Caries risk assessment. CAMBRA CRA tools (CRAs) have been evaluated in several clinical outcomes studies and clinical trials. Updated CAMBRA CRAs for ages 0-6 years and 6 years through adult are provided. These CRAs have been refined by the addition of a quantitative method that will aid the health care provider in determining the caries risk of individuals. Caries management based upon risk assessment. Guidelines for individualized patient care are provided based upon the caries risk status, results of clinical exams and responses of the patient to questions in the CRA. These guidelines are based upon successful outcomes documented in several clinical outcomes studies and clinical trials. The paper includes a review of successful caries management procedures for children and adults as previously published, with additional emphasis on correct use of silver diamine fluoride (SDF) for children. The caries management plan for each individual is based upon reducing the caries risk factors and enhancing the protective factors with the additional aid of behavior modification. Beneficially altering the caries balance is coupled with minimal intervention restorative dentistry, if appropriate. These methods are appropriate for the management of dental caries in all patients.